2018
DOI: 10.1249/mss.0000000000001717
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Accelerometer System for Classifying Physical Activity in Children and Adults

Abstract: When previous wear time compliance results are taken together with our findings, it represents a promising step forward for monitoring and understanding 24-h time-use behaviors. The next step will be to examine the generalizability of these findings in a free-living setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 27 publications
6
46
0
Order By: Relevance
“…The hip- and wrist-based models achieved 91.0% and 88.4% accuracy, respectively. In a study by Stewart et al [ 17 ] a dual-accelerometry system was evaluated with both children and adults for the identification of six activity types. One device was worn at the thigh and another device worn on the lower back.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hip- and wrist-based models achieved 91.0% and 88.4% accuracy, respectively. In a study by Stewart et al [ 17 ] a dual-accelerometry system was evaluated with both children and adults for the identification of six activity types. One device was worn at the thigh and another device worn on the lower back.…”
Section: Discussionmentioning
confidence: 99%
“…However, the size and bulky design of the ActiGraph GT3X device does not make the proposed method by Skotte et al [ 16 ] applicable for use with smaller children. In the study by Stewart et al [ 17 ], a smaller open source Axivity AX3 (Axivity, Newcastle, UK) device was used for the identification of children’s activity types using accelerometers worn at the thigh and trunk in addition to the use of a more advanced machine learning method in the data processing [ 17 ]. However, besides the use of an advanced method, the study only provided data for children 7–15 years of age and did not investigate the identification of biking.…”
Section: Introductionmentioning
confidence: 99%
“…Simple cut-point approaches applied to either processed activity counts or raw acceleration signal (i.e., Euclidean Norm Minus One -ENMO) provide misleading estimates of movement behaviour because they do not account for upper limb movements during sedentary or stationary light-intensity activities [20,21]. In investigations where sitting time is of primary interest, assessments of posture with thigh mounted accelerometers, alone or in combination with other placements, should be considered [22,23]. The findings of the Steene-Johannessen study highlight the long-standing methodological issue of how to operationalise compliance with physical activity guidelines in accelerometer-based studies [24].…”
Section: Stewart G Trostmentioning
confidence: 99%
“…In addition, although Axivity monitors have been shown to be reliable measuring physical activity in over 100,000 participants 94 , with primary school aged children, most research uses waist-worn Actigraph accelerometers 19 95 , while the one study that used Axivity Ax3 accelerometers had them mounted with tape on the waist 96 . It is suggested that when using Axivity accelerometers in children, a dual-accelerometer system with sensors placed on the thigh and the back should be included for greater accuracy 97 . However, this may not be a viable option for school-based research in young children.…”
Section: Study Limitationsmentioning
confidence: 99%